Supersaturation of Dissolved Hydrogen and Methane in Rumen of Tibetan Sheep - Wang, Min; Ungerfeld, Emilio M.; Wang, Rong; Zhou, Chuan She; Basang, Zhu Zha; Ao, Si Man; Tan, Zhi Liang (Frontiers in Microbiology, 2016)
Hydrogen (H2) is an essential substrate for methanogens to produce methane (CH4), and also influences pathways of volatile fatty acids (VFA) production in the rumen. Dissolved H2 (H2 (aq)) is the form of H2 available to microbes, and dissolved CH4 (CH4 (aq)) is important for indicating methanogens activity. Rumen H2 (aq) concentration has been estimated by assuming equilibrium with headspace gaseous H2 (H2 (g)) concentration using Henry’s law, and has also been directly measured in the liquid phase in some in vitro and in vivo experiments. In this in vivo study, H2 (aq) and CH4 (aq) concentration measured directly in rumen fluid and their corresponding concentrations estimated from their gaseous phase concentrations, were compared to investigate the existence of equilibrium between the gas and liquid phases. Twenty-four Tibetan sheep were randomly assigned to two mixed diets containing the same concentrate mixed with oat grass (OG diet) or barley straw (BS diet). Rumen gaseous phase and contents were sampled using rumenocentesis and oral stomach tubing, respectively. Rumen H2 (aq) and CH4 (aq) concentration and VFA profile differed between sheep fed the OG and BS diets. Measured H2 (aq) and CH4 (aq) concentration were greater than H2 (aq) and CH4 (aq) concentrations estimated using gas concentrations, indicating lack of equilibrium between gas and liquid phase and supersaturation of H2 and CH4 in rumen fluid. As a consequence, Gibbs energy changes (∆G) estimated for various metabolic pathways were different when calculated using dissolved gases concentrations directly measured and when using dissolved gases concentrations assuming equilibrium with the gaseous phase. Dissolved CH4, but not CH4 (g), was positively correlated with H2 (aq). Both H2 (aq) and H2 (g) concentrations were positively correlated with the molar percentage of butyrate and negatively correlated with the molar percentage of acetate. In summary, rumen fluid was supersaturated with both H2 and CH4, and H2 (aq) was closely associated with the VFA profile and CH4 (aq) concentration. The assumption of equilibrium between dissolved gases and gaseous phase affected ∆G estimation.